2018
DOI: 10.5194/hess-2018-380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copula and ARMA based study of controlled outflow at Farakka barrage

Abstract: Abstract. In this study, 25 years mean monthly out flow discharge data of Farakka barrage was used (i.e., from 1949 to 1968). Farakka barrage is located between on Ganga River. Spatial and temporal variation in flow rate for any particular area is very common due to various meteorological and other factors existing in nature. But large variations in these factors cause extreme events (e. g., floods and droughts). Monthly outflow discharge for a particular critical month are predicted using statistical models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Overall it is concluded that for the significant correlation among rivers, our proposed C-Vine based CEEMDAN-R-MM and for the non-significant association between rivers, our first-stage proposed model CEEMDAN-R-MM performs well over the works of Ledolter (1978) and Singh et al (2018). It is concluded that the performance of multi-site river inflow data can enhance by providing the maximum information which exists between complex multivariate time series data.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Overall it is concluded that for the significant correlation among rivers, our proposed C-Vine based CEEMDAN-R-MM and for the non-significant association between rivers, our first-stage proposed model CEEMDAN-R-MM performs well over the works of Ledolter (1978) and Singh et al (2018). It is concluded that the performance of multi-site river inflow data can enhance by providing the maximum information which exists between complex multivariate time series data.…”
Section: Discussionmentioning
confidence: 82%
“…However, for the Jhelum and the Chenab rivers inflow as they did not provide any significant correlation among pairs of variables as depicted in Fig. 9, only the first-stage model (CEEMDAN-R-MM; Nazir et al, 2019), provides satisfactory results for Jhelum and Chenab rivers inflow than all other existing work of Ledolter (1978) and Singh et al (2018) and two-stage novel C-Vine based CEEMDAN-R-MM model. It can be observed from our results that by utilizing important information that is present in data, one can enhance the quality of complex hydrological time series data.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations